A Subtitling Analysis Of Imperative Sentences In The Hobbit : The Battle Of The Five Armies Into Pertempuran Lima Tentara - Saputri, Vernanda Ayu; , Dr. Dwi Haryanti, M.Hum; , Mauly Halwat Hikmat, Ph. D (2016)
The objectives of this study are to classify the types of imperative sentence in subtitling and to describe the equivalence and non equivalence of the imperative sentence with the target language in The Hobbit: The Battle of The Five Armies movie. The researcher employs descriptive qualitative method. By this method, the researcher uses the subtitling of The Hobbit: The Battle of The Five Armies as the source data, and the data are imperative sentences. The writer uses obeservation in collecting data. The collected data are analyzed by comparison method. The results of this research paper shows that first, the researcher finds 325 data of imperative sentences and there are 4 types of imperative sentence, namely (1) imperative sentence without subject consisting 200 data or 61,54%, (2) imperative sentence with subject consisiting 103 data or 31,70%, (3) imperative sentence with let consisting 4 data or 51,23%, (4) negative imperative sentence consisting 18 data or 5,53%. The second, the researcher finds 1258 data of equivalence subtitling, there are 1203 data or 95,63% belongs to equivalence subtitling and 55 data or 4,37% belongs to non-equivalence subtitling. So, the translation of subtitling The Hobbit: The Battle of The Five Armies is good. Keywords: subtitling, imperative sentence, equivalence, non-equivalence.